Wiggins, G., & McTighe, J. (2005) Understanding by design (2nd ed.). Alexandria, VA: association for supervision and curriculum development ASCD - Dávila Rubio, Alejandro Mauricio (Colombian Applied Linguistics Journal, 2017)
Writers and curriculum experts Grant Wiggins and Jay McTighe present in this second edition of their best-seller Understanding by Design not only a framework to work on curriculum design in a more comprehensive, overarching, and thorough way but also a pedagogical as well as educational perspective that encourages teachers, students, administrative staff, and even policy makers, to reconsider the purpose, objectives, and impact that a thoughtful curriculum design can have for the community in which it is implemented. In this book, the authors provide a clear depiction of both the theoretical foundations and the practical elements putting everything together for the construction of the design of learning. The different chapters follow their three-staged backward design idea which I consider useful for a full understanding of this innovative way of planning and designing a curriculum.